Study on the cutting force in machining of aluminum honeycomb core material. (15th March 2017) - Qiu, Kunxian; Ming, Weiwei; Shen, Lifeng; An, Qinglong; Chen, Ming
Abstract: Honeycomb sandwich structure has been widely used in the aerospace industry due to its high strength and stiffness to weight ratio. But the poor machinability of honeycomb core is a key factor that limits its application owing to its weak rigidity in in-plane direction of cellular materials. This paper introduced typical machining defects and studied the machining characteristics of honeycomb core. Almost all the cutting burrs and defects were found to locate on the line with entrance angle is equal to 80° and 170°. A cutting force model was proposed to predict the milling force under different spindle speed, feed rate and tool angle. A series of cutting simulation of honeycomb cell wall with tool blade were conducted to determine the cutting force of a single cell wall. The accuracy of proposed model was verified by a group of experiments under different conditions and the average percentage error is below 5% in Y direction and 10% in X direction.